2019
DOI: 10.4018/978-1-5225-6998-5.ch006
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Cultural Identity on the Space Drawed in Virtual Games and Representatıve

Abstract: The digital culture created in the virtual space provides a more liberal and open environment for the people, with fewer restrictions from real life. The current research on virtual reality self-expression has mainly been discovered as an independent aspect of the real self. The chapter also analyzes the use and perceptions of virtual users in the virtual world by focusing on the construct that creates different virtual cultural experiences. For this purpose, the “Second Life” game, which provides a three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since the emergence of virtual spaces, studies of their effects on self-identity have suggested many theoretical frameworks [1][2][3][4][5][6][7] to understand how these spaces can shape our experiences [8][9][10] and self-representations [11][12][13][14]. As one of the most sophisticated mediums for virtual experiences, virtual reality (VR) [15] has been analyzed in studies that see multiple effects on the self and the views people hold toward reality [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of virtual spaces, studies of their effects on self-identity have suggested many theoretical frameworks [1][2][3][4][5][6][7] to understand how these spaces can shape our experiences [8][9][10] and self-representations [11][12][13][14]. As one of the most sophisticated mediums for virtual experiences, virtual reality (VR) [15] has been analyzed in studies that see multiple effects on the self and the views people hold toward reality [16][17][18].…”
Section: Introductionmentioning
confidence: 99%